West federal taxation - Hoffman, William H. (Thomson/South-Western, 2008)
Delivering the most thorough coverage available on individual taxation, the 2008 edition of WEST FEDERAL TAXATION: INDIVIDUAL INCOME TAXES remains the most effective text for mastering the ever-changing Individual Tax Code. Its accessible, comprehensive, and authoritative presentation of the Tax Code and regulations pertaining to the individual taxpayer covers all major developments in federal taxation--complete with relevant, real-world examples. WFT continues its longstanding emphasis on the importance of careful tax planning and its strong coverage of how taxation is affected by international concerns. It offers opportunities to sharpen critical-thinking and writing skills as well as Internet exercises that proved valuable hands-on experience using online resources to solve tax issues. More than just a textbook, WFT offers a revolutionary experience. Built around the areas identified as the most important, this total integrated solution delivers ultimate flexibility. It also adheres to the recommendations of the Accounting Education Change Commission (AECC) and the American Institute of Certified Public Accountants (AICPA)